Les sens assoupis : La vie sociale et sensorielle des artefacts dans l’espace muséal - Blanchard, Marie-Josée; Howes, David (Anthropologica, 2020)
The Senses Still : The Sensory and Social Life of Indigenous Artifacts in Museums. This study starts from the premise that every artifact is a carrier of culture and an assemblage of sensory properties. It focusses specifically on the regulation of the social and sensory life of artifacts in the museum, where they become subject to the sensory regime of the institution, or “museum sensorium.” In the Western museum this typically means that they are reduced to visible forms. This belies the multisensory environment of their culture of origin. Our analysis centres on three examples of objects on display since 2013 in the exhibition “This Is Our Story. First nations and Inuit in the 21st Century” at the Musée de la civilisation in Quebec City. Archival and ethnographic research reveals that the display practices of the museum failed to respond to the expectations and aspirations of the representatives of the Indigenous cultures concerned. The ontology of the museum, with its static and objectifying propensities, took precedence over indigenous realities, which were more keyed to movement, emotion and embodied knowledge.